Plant-Induced Transgenerational Plasticity Affecting Performance but Not Preference in a Polyphagous Moth - Rösvik, Axel; Lhomme, Patrick; Khallaf, Mohammed A.; Anderson, Peter (Frontiers in Ecology and Evolution, 2020)
Environmental variation experienced by a single genotype can induce phenotypic plasticity in various traits, such as behavioural, physiological and developmental characteristics. It can occur within the lifetime of an individual through within-generation phenotypic plasticity (WGP) or vertically across generations through transgenerational phenotypic plasticity (TGP). However, knowledge about TGP and the co-occurrence of WGP and TGP is still limited. In insect host-plant selection, the ability to alter phenotypic traits through WGP is well documented while the importance of TGP and the possible co-occurrence between the two is largely unknown. Host-plant selection of both larvae and adults of the polyphagous moth Spodoptera littoralis can be modified by previous experience through WGP. Thus, the aim of this study was to investigate if parental host-plant experience can influence host-plant choice behaviour and performance of S. littoralis offspring through TGP. For this, we tested effects of rearing parents on different host plants on the offspring’s first instar larval migration and host plant choice, larval development and adult oviposition. A transgenerational effect on larval development was found, with increased pupal weight on a matching host-plant diet to that of the parent, when larvae were reared on cotton (good larval host plant) while no such effect was found on maize (poor larval host plant). These findings indicate that TGP of S. littoralis progeny development traits may only occur under favourable conditions. Parental diet did not affect larval host plant choice or migration. Furthermore, no effect of parental diet was found on offspring oviposition behaviour, indicating that adult female host-plant selection is governed by innate preference hierarchy and WGP, rather than TGP. Thus, parental diet may influence offspring performance but not behaviour, indicating that WGP is most important for host-plant selection behaviours in S. littoralis, but TGP can affect progeny development. If so, the importance of different types of plasticity may vary among traits of S. littoralis associated with host plant utilisation.